Voice changes meaning: the role of gay- versus straight-sounding voices in sentence interpretation - Fasoli, F. (2020)
Utterances reveal not only semantic information but also information about the speaker’s social category membership, including sexual orientation. In four studies (N = 345), we investigated how the meaning of what is being said changes as a function of the speaker’s voice. In Studies 1a/1b, gay- and straight-sounding voices uttered the same sentences. Listeners indicated the likelihood that the speaker was referring to one among two target objects varying along gender-stereotypical characteristics. Listeners envisaged a more “feminine” object when the sentence was uttered by a gay-sounding speaker, and a more “masculine” object when the speaker sounded heterosexual. In Studies 2a/2b, listeners were asked to disambiguate sentences that involved a stereotypical behavior and were open to different interpretations. Listeners disambiguated the sentences by interpreting the action in relation to sexual-orientation information conveyed by voice. Results show that the speaker’s voice changes the subjective meaning of sentences, aligning it to gender-stereotypical expectations.